Understory plant diversity and dominance along the Selo hiking trail of Mount Merbabu, Central Java, Indonesia - DAVINA ALIFIA TSURAYYA; DIAN RAHMAD RENALDI; DINARA AFRIDA SALEH; DITA OKTAVIA; ADITYA WISNU SYAHPUTRA; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2026)
Abstract. Tsurayya DA, Renaldi DR, Saleh DA, Oktavia D, Syahputra AW, Setyawan AD. 2026. Understory plant diversity and dominance along the Selo hiking trail of Mount Merbabu, Central Java, Indonesia. Biodiversitas 27 (7): d270727. https://doi.org/10.13057/biodiv/d270727. Understory vegetation contributes substantially to forest biodiversity and can respond rapidly to environmental conditions, recreational disturbance, and biological invasion. This study characterized understory plant diversity, composition, dominance, and spatial occurrence along the Selo hiking trail in Mount Merbabu National Park, Central Java, Indonesia. Seventy-five 1×1 m quadrats were systematically distributed among three trail zones, comprising five transects and 25 quadrats per zone. Twenty-nine taxa representing herbs, grasses, sedges, ferns, lycophytes, and low shrubs were recorded. Shannon diversity was descriptively similar among zones, with H′ values of 3.270, 3.228, and 3.150 from Basecamp-Post 1 to Post 2-Post 3, respectively, representing a descriptive decline of 0.120. Relative frequency was normalized before calculation of the two-component Importance Value Index (IVI: RD + RF), for which the community total is approximately 200 percentage points. Lophatherum gracile had the highest IVI (13.36), followed by Lepisorus macrosphaerus (12.83), Polystichum braunii (12.46), and Asplenium tenerum (12.25). Ageratina riparia occurred in 78.7% of quadrats and had an IVI of 9.70, supporting its priority for monitoring given independent evidence of its alien and invasive status in Javan mountain ecosystems. Because plot-level abundance matrices, exact archived occupied-quadrat counts for all taxa, vouchers, standardized environmental measurements, and off-trail controls were unavailable, the findings should be interpreted as a descriptive trail-corridor baseline. Repeated, spatially replicated surveys with verified taxonomy and archived plot-level data are recommended.